EFEKTIVITAS EDUKASI ASI DENGAN VISUALISASI PRAKTIK TERHADAP KESIAPAN MENYUSUI PADA IBU HAMIL - Risna Dewi Yanti; Maya Astuti; Enung Harni Susilawati (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2021)
Variation of programs and strategies have been developed by the government to socialize the importance of exclusive breastmilk to mothers and families. One of them is through the pregnancy class in some integrated healthcare centers. However, it is not enough to increase the readiness of mothers to breastfeed their kids. Interesting media and methods that have longer memory retention are needed to deliver the information about breastmilk. One of the method is visual practice, which deliver information through the combination of narration, video, pictures, symbols, analogical stuff and practice. The objective of this aim of this research is to discover the effectiveness of visual practice education on the breastfeeding readiness of pregnant mothers. This research is quantitative research with quasi experiment design, The research used two group pre-test post-test approach. The research was located in Bogor with 20 pregnant mothers in each group as the sample of this research. The data are collected with the breastfeeding readiness questionnaire that was given before and after the intervention is done. Bivariate analysis was done is Mann Whitney. The result found that there is a significant difference in breastfeeding readiness (p<0,05). It is recommended to use this method as one of the methods to promote lactation health preparation.